STRUKTUR UMUR PENDUDUK DAN KEMISKINAN DI KABUPATEN ACEH BESAR - Teuku M. Al-Hasansyah; M. Ilhamsyah Siregar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstrac This study aims to analyze the relationship between the age structure of the population and the level of poverty in Aceh Besar District. Variables in this study include the structure of the population's age, poverty, population education level, and occupation of the population. In conducting this research, the authors used a qualitative analysis method with secondary data obtained from the BPS SUSENAS (National Socio Economic Survey) in 2018. The use of this method aims to describe the characteristics of the population of Aceh Besar who are below the poverty line. The results showed that the level of poverty vulnerability in Aceh Besar was quite high. This is because the average level of education of the population is high school, so productivity is not too high. In addition, opportunities for the labor force to work in the formal sector are also relatively limited, which results in relatively low income levels. Most of Aceh Besar's population also works in primary sectors, where the added value of production is relatively small. Due to the low education and profession of the population in the primary sector, the majority of the middle-aged population (30-44 years) dominates very low and low incomes.Keywords: Population Age Structure, Poverty, Population Education Level, Population Work, Aceh Besar.